Factors associated with potentially problematic opioid prescriptions among individuals with private insurance and medicaid. (November 2019) - Ali, Mir M.; Tehrani, Ali B.; Mutter, Ryan; Henke, Rachel Mosher; Cutler, Eli; Pines, Jesse M.; Mazer-Amirshahi, Maryann
Abstract: If opioid analgesics are prescribed and used inappropriately, they can lead to addiction and other adverse effects. In this study, we (1) examine factors associated with potentially problematic opioid prescriptions and (2) quantify the link between potentially problematic prescriptions and the development of opioid use disorder. We found that older age; female sex; having back pain, arthritis, or migraine; hydrocodone prescription; previous pharmacotherapy for opioid use disorder; and frequent emergency department use were associated with problematic prescriptions among individuals with Medicaid and private insurance. Patients with commercial insurance and Medicaid who had potentially problematic opioid prescriptions were eight and three times more likely, respectively, to develop an opioid use disorder than patients without potentially problematic opioid prescriptions. Our findings help identify factors associated with problematic prescriptions and underscore the importance of targeted public health interventions. Highlights: Private insurance enrollees with problematic opioid prescription were eight times more likely to develop OUD. Medicaid enrollees with problematic opioid prescription were three times more likely to develop OUD. Health plan, ED visits, mental health diagnosis associated with problematic opioid prescription: private insurance enrollees. Non-Hispanic White, ED visits, mental health diagnosis associated with problematic opioid prescription: Medicaid enrollees.